Configuração das capacidades políticas das subsidiárias de multinacionais operando no Brasil - Caldeira Filho, Carlos Afonso (2016)
This study focuses on the phenomenon of the design of political capabilities by subsidiaries of multinationals operating in Brazil. The subsidiaries of MNE's operating in developing countries have the challenge of using political actions while suffering conformity pressures, both from the MNE´s headquarters and from local actors. The Brazil served as a natural laboratory to achieve the objectives of this research. The county qualifies as a good setting for the research because there are evidence of strong political activity by the MNE's in the country, as well as ne should expect the 'type of capitalism' in Brazil to be reflected in the subsidiaries political capabilities. This research presents the case study of the configurations of political capacities of the subsidiaries operating in Brazil and contributes to the current knowledge in three ways. The first contribution is the proposition of a theoretically-grounded model for political capacities. The second contribution is the description and analysis of the configuration of political capabilities used by subsidiaries operating in Brazil, as well as the theoretical discussions resulting from this case. The case describes the particular use of relational and reputation based resources. The case also describes that political capabilities are primarily locally developed. This has implications for the literature of political capability transfer and institutional duality on political capabilities development. The final contribution is the description and proposal of a specific type of political capability design, in the case of companies’ with significant share of government sales as a percentage of total sales.